2020
DOI: 10.1002/anie.202009278
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Lability Modulated by a Valence Electron Moving in and out of 25‐Atom Gold Nanoclusters

Abstract: The emergence of atomically precise metal nanoclusters with unique electronic structures provides access to currently inaccessible catalytic challenges at the single‐electron level. We investigate the catalytic behavior of gold Au25(SR)18 nanoclusters by monitoring an incoming and outgoing free valence electron of Au 6s1. Distinct performances are revealed: Au25(SR)18− is generated upon donation of an electron to neutral Au25(SR)180 and this is associated with a loss in reactivity, whereas Au25(SR)18+ is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…These results indicate that 4-NP is more easily adsorbed on 2, which accounts for the superior activity of 2. [37,46] This study demonstrates that the electronic structure of a metal nanocluster can be modulated via the combination of ligands, and the catalytic performance can thus be improved.…”
Section: Angewandte Chemiementioning
confidence: 77%
See 1 more Smart Citation
“…These results indicate that 4-NP is more easily adsorbed on 2, which accounts for the superior activity of 2. [37,46] This study demonstrates that the electronic structure of a metal nanocluster can be modulated via the combination of ligands, and the catalytic performance can thus be improved.…”
Section: Angewandte Chemiementioning
confidence: 77%
“…For example, Zhu et al. reported that the stable 8‐electron [Au 25 (SCH 2 CH 2 Ph) 18 ] − showed lower catalytic activity than the unstable 7‐electron Au 25 (SCH 2 CH 2 Ph) 18 in the intramolecular hydroamination of 2‐ethynylaniline [37] . Therefore, the balance between stability and activity of cluster catalysts should be taken into consideration in terms of pursuing high catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Because both clusters have enough space for the adsorption of 4‐NP, the influence of steric effects is believed to be minor in terms of the calculation of Gibbs free energy, which suggests that it is mainly affected by the electronic structures. These results indicate that 4‐NP is more easily adsorbed on 2 , which accounts for the superior activity of 2 [37, 46] . This study demonstrates that the electronic structure of a metal nanocluster can be modulated via the combination of ligands, and the catalytic performance can thus be improved.…”
Section: Resultsmentioning
confidence: 70%
“…This further accelerates the production and movement of electrons, thereby boosting the POD-like activity of COF-CNT. [22] The occurrence of polarization is not affected by the direction of COF-CNT in the electric field. Furthermore, the degree of surface polarization increases with an increase in the voltage of the electric field, which can be benefited from the self-driven TENG with a high voltage output.…”
Section: Performance and Mechanism Of Teng-catsystemmentioning
confidence: 98%